Fluorescence Characteristics of Humic Acid in Chinese Black Soil under Long-Term Fertilization - Dan Wei; Yan Li; Shan-shan Cai; Liang Jin; Yu-mei Li; Wei Wang; Yang Bai; Yu Hu; Nicholas Clarke (Advances in Polymer Technology)
Humic substances are important indicators of soil fertility. The fluorescence properties of humic acids from black soils in Harbin, northeast China, were investigated, after long-term fertilization using treatments with or without mineral fertilizer (NPK) and organic manure. Excitation and emission matrices combined with parallel factor analysis were used to investigate the structure of the humic acid. Principal component analysis was performed to select the most suitable parameters for the description of humic acid. The dimension reduction for the original fluorescence parameters extracted two principal components. By using the two principal component scores as a new index for clustering, it was concluded that long-term fertilization treatments in black soil in Harbin clustered into three groups of manure + NPK and organic manure treatments, NPK treatment, and soil without any fertilization. Manure + NPK fertilization and manure fertilization alone led to a higher degree of humification than NPK only or the control. We conclude that long-term fertilization with organic matter with or without NPK could increase the humification degree of these soils.